Potential Impact of 3% Hypertonic Saline Infusion on Tramadol Poisoning-Induced Electrocardiogram Changes; a Randomized Clinical Trial - Omraninava, Ali; Mehdizade, Ahmad; Karimi, Ebrahim; Ghabousian, Amir (Archives of Academic Emergency Medicine, 2022)
Introduction: Tramadol is a synthetic analgesic with weak mu-opioid receptor agonist activity. Tramadol overdose is associated with adverse cardiac effects due to inhibiting cardiac Na+ and K+ channels. This study aimed to investigate the potential ameliorative role of 3% hypertonic saline on the electrocardiogram (ECG) changes in patients presenting with tramadol poisoning. Methods: This was a single-center, controlled, randomized, single-blind clinical trial. Patients were randomized into the case (received hypertonic saline) and control (received placebo) groups. ECG was obtained twice in each group (upon arrival and following the intervention). Response to therapeutic interventions was evaluated using Wilcoxon Signed Ranks Test. Results: A total of 76 patients were included. The mean age of patients was 24.88 ± 4.29 years, and 62 (81.6%) were male. The mean ingested dose of tramadol was 1673.68 ± 608.85 (range: 550-2750) mg. The number needed to treat and the absolute risk reduction of 3% hypertonic saline in the treatment of wide QRS were 1 (95% CI: 1.00 – 1.00) and 100%, respectively. In the treatment of long QTc, these measures were 1.9 (95%CI: 1.2 – 4.5) and 53.85% (95%CI: 22.00 – 85.69), respectively. Conclusion: Given that hypertonic saline infusion can significantly ameliorate tramadol-mediated ECG changes, including QRS prolongation and QT lengthening, it can be regarded as a potential therapeutic strategy to prevent the development of life-threatening ventricular arrhythmias caused by tramadol toxicity.